Comparative effects of dual-task training versus combined exercise training in water and on land on patients with multiple sclerosis: a study protocol of a randomised factorial trial - Sahar Nazary Soltan Ahmad; Seyed Sadredin Shojaedin; Mehdi Khaleghi Tazji (BMJ Open)
Introduction People with multiple sclerosis (PwMS) experience cognitive and motor impairments, including cognitive training and exercise training. This study compares dual task and combined exercise training in water and on land. Water-based training may enhance cognitive and motor function more effectively than land-based training, presenting a promising intervention for PwMS. We explore dual-task training (DTT), including cognitive and motor exercise, with combined exercise in water and on land on the cognition, balance and gait PwMS.Methods and analysis This is a double-blind 3*2*2 factorial randomised trial. Participants will be randomly allocated to one of six groups: four intervention groups and two control groups. All patients will receive supervised 12-week training sessions, two times per week, and will be assessed by a blinded outcome assessor before and at the end of the 12-week programme. The primary outcome includes the Symbol Digit Modalities Test. The secondary outcomes involve the California Verbal Learning Test-II, the Brief Visuospatial Memory Test—Revised, kinetics and kinematics throughout the balance and gait cycle. All the data will be analysed by a blinded data analyst.Ethics and dissemination Ethical approval was granted by the Sports Science Research Institute (No. IR.SSRC.REC.1401.082). The results of the trial will be submitted for publication in journals and distributed to PwMS and physiotherapists.Trial registration number The trial is prospectively registered on 22 March 2024, at https://www.umin.ac.jp/ with an identification number (UMIN000053947).